2017
DOI: 10.11002/kjfp.2017.24.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Change of physicochemical properties, phytochemical contents and biological activities during the vinegar fermentation of Elaeagnus multiflora fruit

Abstract: This study evaluated the changes of physiochemical properties, phytochemical contents, and biological activities during the vinegar fermentation of Elaeagnus multiflora fruit. The contents of pH and reducing sugar decreased from 3.55 and 6.88 mg/mL 3.34 and 2.13 mg/mL, respectively. However the acidity increased from 0.48% to 5.48% during the vinegar fermentation. The alcohol contents increased up to a maximum value of 6.6% at 20 days, and it then decreased at the end fermentation days (2.0%). The viable numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…The vinegar could prolong absorption of triglycerides by inhibiting lipase, and, subsequently, decrease plasma lipid concentration. It was reported the inhibitory activity of pancreatic lipase increased during vinegar fermentation of Elaeagnus multiflora fruit ( Cho et al, 2017 ). Kim et al (2018) reported that the inhibitory activity of pancreatic lipase in carrot vinegar is higher than that of carrot juice.…”
Section: Discussionmentioning
confidence: 99%
“…The vinegar could prolong absorption of triglycerides by inhibiting lipase, and, subsequently, decrease plasma lipid concentration. It was reported the inhibitory activity of pancreatic lipase increased during vinegar fermentation of Elaeagnus multiflora fruit ( Cho et al, 2017 ). Kim et al (2018) reported that the inhibitory activity of pancreatic lipase in carrot vinegar is higher than that of carrot juice.…”
Section: Discussionmentioning
confidence: 99%
“…[18] tarafından mazafati İran hurması sirkesi için bildirilen toplam asitlik değerine (%1. 19) yakın bulunurken, KW sirkesinin toplam asitlik değeri (%1.98) Tomar ve ark. [24] tarafından yaban mersini sirkesi için bildirilen toplam asitlik değerine (%1.96) yakın bulunmuştur.…”
Section: Fizikokimyasal Analizler Toplam Asitlik Ve Phunclassified
“…Sirkenin sağlık üzerindeki faydaları ve üretimi için artan tüketici talebi hurma, kırmızı iğde, yaban mersini, ananas kabuğu, kızılcık, incir, nar, kayısı, mandalina ve kuşburnu gibi çeşitli kaynaklardan sirke üretimi ile ilgili çalışmalara yol açmıştır [18][19][20][21][22][23][24]…”
Section: Introductionunclassified
“…Phytochemicals은 채소나 과일에 함유된 식물성 화학물질로 세포손상 억제 및 면역기능 향상에 도움을 주는 물질이며 현재 까지 밝혀진 종류는 1만여 종 이상에 이르며 종류별로 효능이 다양한 것으로 보고되었다 [5]. 특히 phytochemicals 화합물은 채 소나 과일뿐만 아니라 식용 및 약용작물에도 많이 함유되어 있 다.…”
Section: 서 론unclassified